O processo da alocação dos custos indiretos de fabricação nas indústrias de alimentos no Estado da Paraíba: estudo de casos - Patriota, Maria Salete (2012)
The objective of this research was to verify the allocation process of indirect costs incurred by three food industries in the city of Camp in a Grande, state of Paraíba, comparing the allocation methods of these corporations with those proposed by the pertinent literature (CHAPTER I). Pursuing the best understanding of the relationship between the theory and practice of indirect costs allocations, a review of that literature, with some concepts and classifications of such costs was presented, as well as concernents about the allocation process, considering four basic purposes of accounting costs: Inventory Evaluation, Cost-Based Pricing, Performance Evaluation and Decision An alysis (CHAPTER II). We have decided to use the method of case study, due to the lack of experiment a data in this area , the limitation of this research which included only three industries an à the need o f a deeper description about the current practices of allocation (CHAPTER III) • Next, we have presented the cases, studied and the description of the allocation methods incurred by the referred corporations (CHAPTER IV). The results obtained, have enabled us to analyse the allocation methods focused in this research, comparing them with the purposes of the literature that has been reviewed (CHAPTER V). Finally, we have presented a summary, with our conclusions in this area of knowledge, including suggestions to new studies (CHAPTER VI).